The dual nature of blazar fast variability: Space and ground observations of S5 0716+714. Issue 1 (17th November 2020) - Raiteri, C M; Villata, M; Carosati, D; Benítez, E; Kurtanidze, S O; Gupta, A C; Mirzaqulov, D O; D'Ammando, F; Larionov, V M; Pursimo, T; Acosta-Pulido, J A; Baida, G V; et al.
ABSTRACT: Blazar S5 0716+714 is well-known for its short-term variability, down to intraday time-scales. We here present the 2-min cadence optical light curve obtained by the TESS space telescope in 2019 December–2020 January and analyse the object fast variability with unprecedented sampling. Supporting observations by the Whole Earth Blazar Telescope Collaboration in B, V, R, and I bands allow us to investigate the spectral variability during the TESS pointing. The spectral analysis is further extended in frequency to the UV and X-ray bands with data from the Neil Gehrels Swift Observatory . We develop a new method to unveil the shortest optical variability time-scales. This is based on progressive de-trending of the TESS light curve by means of cubic spline interpolations through the binned fluxes, with decreasing time bins. The de-trended light curves are then analysed with classical tools for time-series analysis (periodogram, autocorrelation, and structure functions). The results show that below 3 d there are significant characteristic variability time-scales of about 1.7, 0.5, and 0.2 d. Variability on time-scales 0.2 d is strongly chromatic and must be ascribed to intrinsic energetic processes involving emitting regions, likely jet substructures, with dimension less than about 10 −3 pc. In contrast, flux changes on time-scales 0.5 d are quasi-achromatic and are probably due to Doppler factor changes of geometric origin.